The Effectiveness of Integrated Antenatal Care Services at IIKNU Tuban in Improving the Health and Awareness of Pregnant Women - Qoyimah, Ilmiatus; Safa'ah, Nurus; Ilmiatus (Jurnal Penelitian, 2024)
This study evaluates the effectiveness of integrated Antenatal Care (ANC) services at IIKNU Tuban in improving maternal health and awareness among pregnant women. Integrated ANC, which combines routine medical care, nutritional education, and early detection of pregnancy complications, has been shown to significantly reduce maternal and neonatal morbidity and mortality globally. Despite improvements in healthcare delivery, challenges such as inadequate access to services and cultural barriers persist, especially in rural areas. Data collected from pregnant women at IIKNU Tuban indicated that the program has successfully increased maternal awareness regarding the importance of regular ANC visits, nutritional needs, and the identification of potential complications. Participants also reported better health outcomes, such as improved nutritional status and a reduction in anemia. However, challenges, including staffing shortages and the limited availability of advanced medical resources, continue to affect the program's overall impact. The study concludes that while integrated ANC services at IIKNU Tuban are effective in improving maternal health, addressing resource constraints and cultural barriers is crucial for further enhancing program effectiveness. These findings suggest that localized, integrated ANC programs could serve as a model for other regions aiming to improve maternal health outcomes in underserved populations.